Exploring the Knowledge and Attitudes of Mothers on Utilisation of Maternity Services in Peri urban District of Central Uganda. A Cross-sectional Study. - Nalutaaya, Janet; Walekhwa, Abel Wilson (Student’s Journal of Health Research Africa, 2022)
Background In Mende sub-county, out of about 1904 pregnant women, only 316 (17%) institutional deliveries were done with 592 having had at least one antenatal care visit and only 225 reaching the fourth Antenatal care visit in Financial Year 2019/20. We, therefore, sought to explore the knowledge, and attitudes of women and how they influenced maternal health services utilization in a rural sub-county of Wakiso district in Uganda. Methods We conducted a cross-sectional study using quantitative methods. The study was conducted at Show Mercy International Health Centre in Mende sub-county - Wakiso District from March to April 2016. A total of 70 participants were enrolled in the study. We used open-ended questionnaires to collect data from the study participants, quantitative data were collected, coded, and analyzed using Microsoft excel windows 16, and SPSS version 16.0. Results Of the 70 mothers, the majority were aged 28-37 years (57.1%) with a mean age of 33.5 years, Majority (44.3%) had attained both Secondary followed by primary level education (34.3%). The majority of the women (45.7%) had some form of employment although a good number of them (28.6%) were peasants and casual labourers. We found out that 92.9% were knowledgeable about maternal health services. Furthermore, 46.9% of mothers preferred both Antenatal care and delivery services at the health facility. Conclusion The majority of the mothers were knowledgeable about health facility maternal health services and reported their willingness to use them. The motivating factors for health facility deliveries were (1) healthy baby and pregnancy, (2) getting Mama Kits and mosquito nets, and (3) accessing Prevention of Mother to Child treatment services and routine supplements. Recommendations: Further sensitization for HIV/AIDS testing during pregnancy but also maintain the supply of Mama Kits and mosquito nets for improved health facility deliveries.